ANALISIS RASIO PROFITABILITAS DAN LIKUIDITAS TERHADAP KINERJA KEUANGAN CV. SENTRA LOGAM PANGKALPINANG - Anderson; Shinta Lestari, Deara; Tri Setyo Mulyani, Hendarti (Jurnal Progresif Manajemen Bisnis, 2024)
This thesis was written and compiled by Anderson with a 640200020 student Master Number entitled "Analysis of the Ratio of Profitability and Liquidity to Financial Performance of CV. SENTRA LOGAM Pangkalpinang". The study was conducted from January 2024 – May 2024, containing 89 pages without attachments. The purpose of this study is to determine the condition of CV. SENTRA LOGAM's financial performance based on profitability ratio and liquidity ratio. This study used a descriptive quantitative method approach. The data source used is secondary data and the type of data used is documentary data. The data analysis technique used in this study is to use profitability and liquidity ratio analysis by applying nominal data and applied through appropriate financial ratio formulas to produce results that can be explained in more detail. The results showed that the condition of financial performance based on profitability ratio, with the percentage measure used, gross profit margin above 5% can be categorized as good, net profit margin and operating profit less than 5% can be categorized as unfavorable. The condition of the company's financial performance based on the liquidity ratio, with the percentage measure used, the current ratio above 100% can be categorized as good, the quick ratio and cash ratio below 100% can be categorized as not good.